Representing e-mail semantically for automated ontology building - Beseiso M.; Ahmad A.R.; Ismail R. (2023)
The Semantic Web represents enormous data available on the World Wide Web in a machine readable format for effective extraction of ontologies providing for effective and relevant information extraction. Research shows that an enormous amount of time is spent on E-Mails for communication and information exchange. Adding semantics to the existing e-mail systems could not only provide for efficient usage of time and resources but also refresh the meaning of e-mail communication. This paper gives future scenario in applying semantic web for E-Mail applications by proposing a new framework intended to add a semantic web layer to the mail server in order to improve the process of linking, integrating, and searching of E-Mails. Also, a new method for semantic E-Mails representation is proposed that will improve the process of ontology extraction from semantic E-Mail. 2012 Springer-Verlag.